Studi Kasus Ibu Melakukan Kunjungan Ulang Pada Balita Pneumonia Di Wilayah Kerja Puskesmas Landasan Ulin Kalimantan Selatan - Eka Handayani; Septi Anggraeni (HB PRESS, 2019)
Acute respiratory infections affect many children, both in developing countries and in developed countries. acute respiratory infections that affect death and often affect children under 5 years of age, namely pneumonia. Pneumonia is the main killer of toddlers in the world with a higher prevalence compared to AIDS, malaria and measles. Every year, it is estimated that more than 2 million children under five die from Pneumonia (1 toddler / 20 seconds) from 9 million total deaths of children under five in the world. In Indonesia, pneumonia is still a big problem considering the mortality rate from this disease is still high.. Knowing the mother's case studies do repeat visits in infants pneumonia in health center Landasan Ulin. A qualitative study through interviews and documentation to one health worker. Not all mothers bring their babies repeated visit only 30% of mothers who commit repeated visit of all children under five suffering from pneumonia. Mother toddler who do repeat visits by 35% means that more mothers who do not do repeat visits by 65% this is because there are several reasons mothers do not bring toddlers pneumonia to re-visit them her son had recovered and did not cough again, there also reasoned mothers are busy.